Upaya Pengembangan Peternakan Sapi Potong Tanpa Limbah di Desa Bentangan Kabupaten Klaten - Ayu Intan Sari; Shanti Emawati (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2020)
Farmer in managing their livestock business less attention to the impact on the environment. The purpose of this community empowerment activity is to especially for farmers and ranchers with the aim of increasing the added value of cattle dung into energy source and solve the problem of environmental pollution, improving public welfare through the cost-efficiency of energy supply and the cost of purchasing organic fertilizers. This activity is carried out in Bentangan village, Wonosari Sub-District, Klaten District. The program is as inclusive as possible group of partners in the implementation or use of Participatory Rural Appraisal (PRA) methods, through focus group discussions, counseling, technology transfer appropriate (installation of biogas and sewage treatment), training and demonstration. The results achieved are already carried out the construction of a biogas installation size of 9 m3 to accommodate faeces 6 cows that can be utilized as a source of 1 stove 2 furnaces, repair the cage floor, assembly and installation of a container of urine. The increased knowledge is shown from the increase in the pre-test and post-test scores 63 increased to 80,7, while the increase in motivation is shown by changes in the attitude of farmers who are increasingly open to environmentally friendly animal husbandry systems through the treatment of livestock manure. The effects of continuation from the IbM implementation, beef cattle farm and food crops would be environment friendly and zero waste.